2013
DOI: 10.1039/c3ob41941j
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship studies of the aromatic positions in cyclopentapeptide CXCR4 antagonists

Abstract: The cyclopentapeptide CXCR4 antagonist FC131 (cyclo(-Arg 1 -Arg 2 -2-Nal 3 -Gly 4 -D-Tyr 5 -), 2; 2-Nal = 3-(2-naphthyl)alanine) represents an excellent starting point for development of novel drug-like ligands with therapeutic potential in HIV, cancer, stem-cell mobilization, inflammation, and autoimmune diseases. While the structure-activity relationships for Arg 1 , Arg 2 , and Gly 4 are well established, less is 10 understood about the roles of the aromatic residues 2-Nal 3 and D-Tyr 5 . Here we report fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…11 However, as the D-Phe 5 analogue was found to be only 2-fold less potent, this H-bond is not essential for antagonistic activity; indeed, the Gly 5 analogue of 1 was found to be only one order of magnitude less potent than 1 in our assay system. 11 Collectively, these observations imply that the remaining L-/D-Arg 1 -Arg 2 -2-Nal 3 tripeptide fragment serves as a recognition motif for peptidic CXCR4 antagonists, which motivates further studies of both flexible and constrained small molecules containing this motif. Through dissection of the cyclopentapeptide structure and a stepwise reintroduction of cyclic constraints, we here report the design, synthesis, and biological evaluation of a novel class of scaffold-based tripeptidomimetic CXCR4 antagonists based on the D-Arg-Arg-2-Nal motif.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 However, as the D-Phe 5 analogue was found to be only 2-fold less potent, this H-bond is not essential for antagonistic activity; indeed, the Gly 5 analogue of 1 was found to be only one order of magnitude less potent than 1 in our assay system. 11 Collectively, these observations imply that the remaining L-/D-Arg 1 -Arg 2 -2-Nal 3 tripeptide fragment serves as a recognition motif for peptidic CXCR4 antagonists, which motivates further studies of both flexible and constrained small molecules containing this motif. Through dissection of the cyclopentapeptide structure and a stepwise reintroduction of cyclic constraints, we here report the design, synthesis, and biological evaluation of a novel class of scaffold-based tripeptidomimetic CXCR4 antagonists based on the D-Arg-Arg-2-Nal motif.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we have recently shown that replacement of L-2-Nal in position 3 with aromatic/alicyclic analogs results in significant reduction of the antagonistic potency, 11 and therefore used a 2-naphthyl group with the appropriate spacer length for all compounds. In contrast, position 1 has been shown to be relatively tolerant to structural and 0.023 µM, respectively).…”
Section: General Design Considerationsmentioning
confidence: 99%
See 3 more Smart Citations